Holistic Management of Mrs. D 68 Years Old with Hypercholesterolemia and Hyperuricemia Through Medical Approach Family - Sinum, Ilham Muhammad; Saftarina, Fitria (Global Health Science Group, 2025)
Factors such as age, gender, family history, unhealthy lifestyle, lack of physical activity can be associated with cardiovascular risk and impact on hypercholesterolemia. Application of family doctor services based on evidence-based medicine to patients by identifying risk factors, clinical problems, and patient management based on a patient problem solving framework with a patient centered and family approach. This is a case report study. Data were obtained from physical examination, and medical records. The assessment was based on a holistic diagnosis from the beginning, process, and end of the study both quantitatively and qualitatively. Mrs. D, 68 years old, came to Health Center with complaints of toe joint pain and neck pain. Patients are worried that their complaints can interfere their activities. Non-medical and medical interventions were carried out on patients and their families with education regarding the patient's illness during three home visits. The evaluation results obtained were that patient complaints decreased and knowledge of patients and their families regarding hyperuricemia and hypercholesterolemia increased. Holistic and comprehensive management of the patient's problems, Mrs. D has been carried out by providing counseling to increase the knowledge of the patient and patient's family.